The Implementation of Process Differentiated Instruction Based on VARK Learning Styles for Junior High School Students in Solving Statistics Problems - Falih Hemi Wibisono Putra; Susi Setiawani; Robiatul Adawiyah; Edy Wihardjo (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
This research, titled "The Implementation of Process Differentiated Instruction Based on VARK Learning Styles for Junior High School Students in Solving Statistics Problems," was prompted by a discrepancy between the Merdeka Curriculum's mandate for diverse learning and the continued use of conventional teaching at SMPN 1 Panti. The study aimed to implement and describe the effects of process-differentiated instruction based on VARK learning styles on students' statistical problem-solving abilities. A quasi-experimental, nonequivalent control group design was employed, involving two eighth-grade classes: an experimental group (n = 29) and a control group (n = 29). The experimental group received process differentiation tailored to VARK styles, while the control group received conventional instruction. Data were collected via pretests and posttests and analyzed using non-parametric statistics. The findings showed no statistically significant difference in problem-solving outcomes between the two groups (Mann-Whitney U, p = 0,151). However, the Wilcoxon Signed-Rank test revealed a significant improvement in the experimental group’s scores from pretest to posttest (p = 0,000). Moreover, student interviews indicated that the differentiated approach significantly increased their motivation and engagement. It was concluded that while the short-term intervention did not yield statistically superior test scores, it profoundly enhanced the learning process and student experience.